Troubling Toys: Rare-Earth Magnet Ingestion in Children Causing Bowel Perforations - Parkash Mandhan; Muthana Alsalihi; Saleem Mammoo; Mansour J. Ali (Hindawi Limited, 2014)
Ingestion of foreign bodies in the pediatric population is common and magnet ingestion is known to cause a significant morbidity. Rare-earth magnets are small 3-6 mm diameter spherical powerful magnets that are sold as popular desk toys for adults and were previously found in construction toys in attractive colors for children to play with. We describe 2 young healthy children who ingested rare-earth magnets Buckyballs while playing with these magnetic toys and later presented in emergency with acute abdomen. Abdominal imaging revealed several (26 and 5) pieces of rare-earth magnets in the bowel loops. Emergency surgical exploration revealed multiple gastrointestinal perforations and fistula formation at sites of bowel entrapment in between strong magnets apposed to one another. We highlight the potential dangers of rare-earth magnets in children and suggest increasing public awareness about risks involved in rare-earth magnets ingestion by children to overcome this serious public health issue.